Effect of sodium ascorbate on dentin bond strength after treatment with oxidizing root canal irrigants† - Nihan Gönülol; Elif Kalyoncuoğlu; Ertan Ertaş (Elsevier, 2015)
Background/purpose: The aim of this study was to evaluate the effect of 10% sodium ascorbate solution on dentin bond strength after being treated with different oxygen-releasing root canal irrigants. Materials and methods: Twenty-one human third molars were used in this study. The specimens were randomly divided into seven groups according to irrigation solutions, as follows: Group C (control group), distilled water; Group SH, 5.25% sodium hypochlorite (NaOCl); Group SHA, 5.25% NaOCl + 10% sodium ascorbate solution; Group HP, 10% hydrogen peroxide (H2O2); Group HPA, 10% H2O2 + 10% sodium ascorbate solution; and Group OW, ozonated water; Group OWA, ozonated water + 10% sodium ascorbate solution. A two-step self-etching adhesive system (CLEARFIL SE Bond) was applied to the surfaces, and resin core buildups (Filtek Z550) were placed. The specimens were sectioned into 1-mm2 beams and tested in a microtensile bond-strength (μTBS) testing machine at a cross-head speed of 1 mm/minute. Fractured specimens were examined with a stereomicroscope to determine the mode of failure (adhesive, cohesive, or mixed). The data were analyzed by one-way analysis of variance and Tukey tests (P < 0.05). Results: The ozonatedwater-treated groups showed the lowest μTBS values among all the groups. Although the 10% sodium ascorbate application increased dentin bond strength in Group OW, the difference was not significant (P > 0.05). Conclusion: Although 10% sodium ascorbate application for 10 minutes is an effective method to reverse the compromised bond strength of NaOCl- and H2O2-treated dentin, it might not have a sufficient effect when the dentin is treated with ozonated water.